INFLUENCE OF PRECURSORS AND SOWING TIME OF WINTER WHEAT ON WINTER HARDINESS AND INFESTATION WITH PHYTOPATHOGENS - Barabolia, O. V.; Liashenko, V. V.; Doronin, S. M.; Polezhak, Ye. Yu. (Scientific Progress & Innovations, 2021)
The article substantiates the topicality of increasing the productivity and quality of winter wheat grain on the basis of little cost, highly effective and environmentally safe measures that are the selection of precursors in crop rotation and sowing time. The purpose of the study is to determine the influence of precursors and sowing time on winter hardiness, diseases and damage with pests of winter wheat plants. Field experiments were carried out according to generally accepted techniques during 2017–2020. To ensure high accuracy of experiments, they were placed in the fields with equaled relief and fertility, which was confirmed by soil and agrochemical surveys materials. The experiments were conducted according to the following scheme: pea; silage corn; 2) sowing time: 01.09; 10.09; 20.09; 30.09; 05.10. The results of the research have shown that the best indicators of winter hardiness of winter wheat plants within were within 3.9–4.8 points, which makes 4.4 points on the average; these indicators were ensured in the case when pea was the precursor. The placement of winter wheat after grain legume to some extent positively affected the development of plants in the autumn period, as well as passing the stages of hardening and, ultimately, increased the general winter hardiness of winter wheat, in comparison with the variants where silage corn was the precursor. The choosing of sowing time was the main factor that affected diseases onset and damage with pests of winter wheat plants According to the results of the research, precursors did not have a significant impact on this process. At the same time, the infestation with powdery mildew was observed less often if the crop was sown after pea. In its turn, fewer plants were affected with brown rust in cases when wheat areas were placed after silage corn. Sowing time of winter wheat had significant impact on diseases and damage with pests. In this case, the following tendency was observed: the percentage of diseases onset and damage with pests of winter wheat plants gradually decreased from earlier than later sowing time.